Accelerated Idioventricular Rhythm and Hypokalemia, Atypical Presentation in the Midst of a Pandemic - Rodríguez-Artuza, Carlos; Torres, Mayela Labarca; Meza, José (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
A 34-year-old female patient was referred to a private center from a rural population due to exertional dyspnea and palpitations for 15 days being previously asymptomatic, a surface electrocardiogram diagnoses sinus rhythm alternating with accelerated idioventricular rhythm with episodes of short-coupling intervals. When conducting a diagnostic investigation, hypokalemia and decreased serum magnesium were evidenced and, after correction of the water-electrolyte imbalance, the electrocardiographic disorders disappeared.